Ginsenosides and other Phytochemicals of Panax spp. Properties and uses in the pharmaceutical field - Solís Vindas, Gretel (2021)
Introduction: Ginseng has been used since ancient times, for its medicinal properties. This plant comes from the genus Panax, and the most representative species are Panax quinquefolium, Panax ginseng, and Panax notoginseng. Methods: In this research, database, books and scientific articles were reviewed from 1999 to 2019, using the following descriptors: Panax, ginsenosides and adaptogens. Results: These plants active components are saponins, known as ginsenosides, and can be classified according to their chemical structure. These are found in different proportions according to the different Panax species. Conclusion: Ginseng is used due to its adaptogenic properties. It also can be used to treat cardiovascular and neurological diseases and to counteract inflammation, cancer, and sexual impotence. Finally, some adverse effects are presented, and formulations containing ginseng are detailed.